Resistance mechanisms and countermeasures in CLDN18.2-positive tumors: from molecular networks to clinical practice - Yutao Xia; Mingfang Wang; Taosheng Huang; Kai Sun; Peng Wang (Frontiers in Oncology, 2026)
Claudin 18.2 (CLDN18.2) has rapidly become a major target in solid-tumor oncology. Zolbetuximab, the first anti-CLDN18.2 antibody, was approved in 2024 for HER2-negative, CLDN18.2-high advanced gastric and gastro-esophageal junction adenocarcinoma, and more than one hundred CLDN18.2-directed trials are now under way across monoclonal antibodies, antibody-drug conjugates, bispecific antibodies and CAR-T cells. As these agents enter the clinic, resistance has become the central challenge. This review synthesizes the resistance mechanisms emerging from this experience and organizes them into six biological dimensions, separating those distinctive to CLDN18.2 from those shared across therapeutic platforms, and pairs each with mechanism-matched countermeasures weighted by level of evidence. From this synthesis we advance a central argument about treatment sequencing: because CLDN18.2 expression declines progressively under therapeutic pressure, continuous target-plus-chemotherapy acts on an eroding antigen substrate. For patients with high, homogeneous baseline expression, an early intensive induction followed by CLDN18.2-directed maintenance may therefore be preferable to indefinite target-plus-chemotherapy. We further consider the tissue-context-dependent biology of CLDN18.2 relevant to patient selection, and outline the prospective, biomarker-embedded trials needed to test these proposals.